(untitled) (Journal of Atomic and Molecular Sciences, 2021)
Using the first-principle method within the generalized gradient approximation, this paper studies the bands structure, structural parameters, and state densities of wide-gap semiconductor material CuYO_2. The calculated results show that, the valence band of CuYO_2 mainly compose of 3d of Cu, and 2p of O; while the conduction band mainly compose of 3d of Y. Through the +U correction, with the increasing of the value of U, the conduction band and valence band of CuYO_2 become split, the peak of 3d of Y move towards high energy area, which induce to the enlarge of conduction band area and band gap; in addition, the minimum of conduction band is transfer L point into Γ point when the value of U is 2eV, which show +U method mainly correct the conduction band of CuYO_2 so that improve the calculated value of band gap.